(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The integration of Artificial Intelligence (AI) in educational settings presents a transformative potential to enhance learning experiences, personalize education, and improve administrative efficiency. However, the adoption of AI technologies in education also poses significant challenges, including ethical considerations, data privacy concerns, and the need for substantial infrastructure investment. This paper explores the opportunities and challenges associated with implementing AI in educational environments. Through a comprehensive review of current literature and case studies, we highlight key areas where AI can make a substantial impact, as well as the barriers that must be addressed to ensure its successful integration.